Anorexia nervosa restricting type has increased in severity over three decades: Japanese clinical samples from 1988 to 2018. Issue 1 (27th November 2020) - Harada, Tomoko; Yamauchi, Tsuneo; Miyawaki, Dai; Miyamoto, Saori; Yoshida, Hisako; Nishimoto, Kazuya; Matsuzuka, Takumi; Honda, Mihoko; Inoue, Koki
Abstract: Objective: Although eating disorders (EDs) surged in the late 1900s and are now recognized worldwide, the time trend of ED characteristics remains unknown. This study aimed to clarify changes in characteristics of anorexia nervosa restricting type (AN‐R) over 30 years. Methods: We conducted a cross‐sectional study and examined 996 female treatment‐seeking patients with AN‐R in Japan from 1988 to 2018. Demographics, body mass index (BMI), and Eating Disorder Inventory scores were compared among three groups in accordance with the time of initial consultation: Group 1 (1988–1998), Group 2 (1998–2008), Group 3 (2008–2018). Results: The mean BMI at the initial consultation significantly decreased by 0.6 kg/m 2 (from 14.0 kg/m 2 in Group 1 to 13.4 kg/m 2 in Group 3). Groups 2 and 3 scored significantly higher in drive for thinness, interpersonal distrust, and interoceptive awareness than those in Group 1. The range of onset age is wider and the number of late‐onset AN‐R with prolonged delay in treatment has increased over time. Discussion: This study shows that AN‐R has increased in physical and psychopathological severity over the past 30 years in Japan. Interdisciplinary research is needed to clarify the relationship between AN‐R and time trend.